Barriers and Challenges in Implementing Green Management Practices: A Study of Corporate Implementation - Sapto Supriyanto; Thomas Chrityanto Matantu (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study explores the barriers and challenges organizations face when implementing green management practices. Through a qualitative approach involving in-depth interviews with 15 key informants and document analysis, the research reveals complex interconnections between organizational, resource-related, and external barriers that impede successful implementation. The findings highlight a